2021
DOI: 10.1088/2516-1091/abfc2c
|View full text |Cite
|
Sign up to set email alerts
|

Advances on gradient scaffolds for osteochondral tissue engineering

Abstract: The osteochondral (OC) tissue is one of the most hierarchical and complex structures known and it is composed by two main compartments of hyaline articular cartilage and subchondral bone. It exhibits unique cellular and molecular transitions from the cartilage to the bone layers. OC diseases such as osteoarthritis and traumatic lesions may affect the articular cartilage, calcified cartilage (interface region) and subchondral bone, thus posing great regenerative challenges. Tissue engineering (TE) principles ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 142 publications
0
8
0
Order By: Relevance
“…[ 36 ] Moreover, several studies also found that stress relaxation is correlated to osteogenesis, with faster stress relaxation significantly improving mesenchymal stem cell (MSC) osteogenic differentiation. [ 24 , 25 , 37 , 38 , 39 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 36 ] Moreover, several studies also found that stress relaxation is correlated to osteogenesis, with faster stress relaxation significantly improving mesenchymal stem cell (MSC) osteogenic differentiation. [ 24 , 25 , 37 , 38 , 39 ]…”
Section: Resultsmentioning
confidence: 99%
“…[36] Moreover, several studies also found that stress relaxation is correlated to osteogenesis, with faster stress relaxation significantly improving mesenchymal stem cell (MSC) osteogenic differentiation. [24,25,[37][38][39] Surface elastic modulus and hardness were determined using nanoindentation (Figure 2f,g). Overall, the melt-printed scaffolds have a higher surface hardness and reduced elastic modulus than solvent-printed scaffolds.…”
Section: Physiochemical Properties Of Melt and Solvent Extruded 3d Pr...mentioning
confidence: 99%
“…Natural joints are composed of cartilage and subchondral bone, which are connected by a dense calcified cartilage layer [52,53]. In the repair of bone joints, it is important to design a scaffold with a continuous gradient in terms of material composition, structure, mechanical properties, and biological performance [54]. Current joint injuries typically involve damage to both cartilage and subchondral bone [55,56].…”
Section: A Bone Scaffold For Repairing Osteochondral Defectsmentioning
confidence: 99%
“…Osteochondral tissue (OCT) is a composite tissue structure, mainly found in the joints of the body, formed by bone and cartilage tissues arranged in a certain pattern [4]. The most important structures are the articular cartilage (AC), the calcified cartilage zone (CCZ) and the subchondral bone (SSB) and In OCT, the AC accounts for 90%, while the SSB accounts for an almost equal proportion to the CCZ at 5% respectively [5].…”
Section: Biological and Mechanical Properties Of Osteochondral Tissuementioning
confidence: 99%